High pressure dynamic XAS studies using an energy-dispersive spectrometer. Issue 3 (2nd July 2016) - Mathon, O.; Occelli, F.; Lescoute, E.; Sollier, A.; Loubeyre, P.; Helsby, W.; Headspith, J.; Torchio, R.; Kantor, I.; Pascarelli, S.
ABSTRACT: We present in this paper recent advances in the high pressure domain provided by the introduction of time-resolved energy-dispersive XAS (EDXAS) techniques at synchrotrons. We highlight technical aspects and describe two modes of acquisition: the 'movie' mode, where the time resolution is given by the detector acquisition speed and the 'pump-and-probe' mode, where the time resolution is given by the delay between the pump and the probe. These two modes define a frontier in the time resolution, respectively above and below the ∼10 μs regime. In the former, examples of applications are chemical stability and reactions at high pressure and high temperature or probing the warm dense matter regime using rapid current ramps. In the latter, an example is given on studies of dynamically compressed matter, by coupling single-bunch EDXAS at high-brilliance synchrotron to a nanosecond high-power laser.